A phase 1, randomized, double‐blind, placebo‐controlled study to evaluate the safety, tolerability, and pharmacokinetics of single and multiple doses of lisdexamfetamine dimesylate in Japanese and Caucasian healthy adult subjects. Issue 1 (25th November 2019) - Ermer, James; Martin, Patrick; Corcoran, Mary; Matsuo, Yumiko
Abstract: Aim: To assess safety, tolerability, and pharmacokinetics of lisdexamfetamine dimesylate in Japanese and Caucasian healthy adults. Methods: A phase 1, double‐blind, randomized, placebo‐controlled, single‐ and multiple‐dose study in Japanese and Caucasian subjects. Subjects received lisdexamfetamine 20 mg or placebo on Day 1, then lisdexamfetamine 20 mg/d (Days 4‐8), 50 mg/d (Days 9‐13), 70 mg/d (Days 14‐18), or matching placebo. Pharmacokinetic parameters for lisdexamfetamine and d ‐ amphetamine were estimated by noncompartmental analysis. Results: Fifteen Japanese and 19 Caucasian subjects were enrolled and randomized. The lisdexamfetamine and d ‐ amphetamine plasma concentration‐time curves were similar for both ethnic groups following single and multiple doses. Mean area under the concentration‐time curves for d ‐ amphetamine were higher (by 11%‐15%) in Japanese than Caucasian subjects following multiple dosing of lisdexamfetamine. Mean bodyweight was 17% lower in Japanese than Caucasian subjects. Weight‐corrected means for oral clearance were similar in both ethnic groups, with no unexpected accumulation of d ‐ amphetamine. Lisdexamfetamine was generally well tolerated by both ethnic groups, with no serious adverse events reported. The 10/12 Japanese and 11/16 Caucasian subjects who received lisdexamfetamine completed the study; two Japanese and three Caucasian subjects discontinued due to adverse events. Most adverse events were of mild severity. Conclusion: Pharmacokinetics were generally similar for Japanese and Caucasian subjects; the minor differences observed were likely due to bodyweight differences in the two ethnic groups. Lisdexamfetamine was generally well tolerated. Adverse events were consistent with the established safety profile of lisdexamfetamine and were similar in both ethnic groups. Abstract : This phase 1, double‐blind, randomized, placebo‐controlled study was conducted to assess safety, tolerability, and pharmacokinetics of lisdexamfetamine dimesylate in Japanese and Caucasian subjects. Fifteen Japanese and 19 Caucasian subjects were enrolled and randomized to receive lisdexamfetamine 20 mg (Day 1), 20 mg/d (Days 4‐8), 50 mg/d (Days 9‐13), and 70 mg/d (Days 14‐18), or matching placebo. Pharmacokinetics were generally similar for Japanese and Caucasian subjects; minor differences observed were likely due to bodyweight differences in the two ethnic groups, and lisdexamfetamine was generally well tolerated.